The Konsep Pendidikan Sosial Berbasis Spiritual Etik:: Telaah Pemikiran Al-Ghazali dalam Adab al-Ṣuḥbah wa al-Mu'āsyarah dan Signifikansinya bagi Masyarakat Modern - Junaidi, M.; Rahmatullah, Asep (Tarbawi : Jurnal Studi Pendidikan Islami, 2026)
Abstract Purpose : This study aims to examine the concept of spiritually ethical–based social education in Imam Al-Ghazali’s Adab al-Ṣuḥbah wa al-Mu‘āsyarah, a work specifically dedicated to the ethics of companionship and social interaction, and to articulate its relevance in addressing the contemporary crisis of individualism, weakening social solidarity, and moral disorientation in modern society. Design/methodology/approach : This study employs qualitative library research with a descriptive-analytical approach. The primary source is Al-Ghazali’s Adab al-Ṣuḥbah wa al-Mu‘āsyarah, supported by relevant secondary literature. Data were analyzed using thematic content analysis combined with a hermeneutic approach to identify key concepts of social education and reconstruct their relevance within contemporary social contexts. Research limitations/implications : This study has certain limitations, as it primarily focuses on describing the social educational values found in Adab al-Ṣuḥbah wa al-Mu‘āsyarah without providing a deeper analytical examination of Al-Ghazali’s epistemological construction and conceptual framework. The research does not fully explore how this model of social education is systematically developed within the broader intellectual project of Ihya’ ‘Ulum al-Din. Future studies are therefore encouraged to investigate its methodological dimensions, ontological foundations, and theoretical relevance through comparative approaches with contemporary social education theories. Findings : The findings reveal that Al-Ghazali’s concept of social education is rooted in the integration of spiritual purification (tazkiyat al-nafs) and moral cultivation within social relationships. Values such as brotherhood, compassion, justice, empathy, and social responsibility are positioned not merely as ethical norms, but as integral components of individual spiritual transformation that ultimately shape social harmony. For Al-Ghazali, social education is inherently spiritual-ethical, as it places inner reform as the foundation for constructing a stable and harmonious society. Originality/value : The originality of this study lies in reconstructing Adab al-Ṣuḥbah wa al-Mu‘āsyarah as a framework of spiritually grounded social education rather than merely a treatise on friendship ethics. This research contributes theoretically by demonstrating the continuing relevance of Al-Ghazali’s thought in addressing moral crises and social disintegration in modern society through an educational approach that integrates spiritual and social dimensions.